PELAKSANAAN PEMENUHAN HAK BURUH PASCA PUTUSAN PENGADILAN HUBUNGAN INDUSTRIAL PADA PENGADILAN NEGERI PEKANBARU - Reza, Muhammad Jourdy; Firdaus, Firdaus; Hendra, Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The Industrial Relations Court is a special court established within thedistrict court which has the authority to examine, adjudicate and make decisionson industrial relations disputes, this is stated in Article 1 paragraph 17 of LawNumber 4 of 2004 concerning Settlement of Industrial Relations Disputes.according to Article 97 of Law Number 2 of 2004 concerning Settlement ofIndustrial Relations Disputes, the decision of the Industrial Relations Courtdetermines the obligations that must be carried out and/or the rights that must beaccepted by the parties or one of the parties for any settlement of industrialrelations disputes. However, the implementation did not run smoothly whichresulted in legal uncertainty and the failure to fulfill the rights of laborers oremployees guaranteed by Article 156 paragraph 1 of Law Number 13 of 2003concerning Employment which states